2019
DOI: 10.1111/btp.12638
|View full text |Cite
|
Sign up to set email alerts
|

Beta diversity and oligarchic dominance in the tropical forests of Southern Costa Rica

Abstract: Recent studies have reported a consistent pattern of strong dominance of a small subset of tree species in neotropical forests. These species have been called "hyperdominant" at large geographical scales and "oligarchs" at regional-landscape scales when being abundant and frequent. Forest community assembly is shaped by environmental factors and stochastic processes, but so far the contribution of oligarchic species to the variation of community composition (i.e., beta diversity) remains poorly known. To that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…However, the clear majority of our indicator species turned out to be host plant generalists, whereas only 23 species (25%) have taxonomically restricted host plant ranges. Among the few indicator species with narrow larval host ranges (one plant family or even one plant genus), affiliations to Moraceae, Urticaceae ( Cecropia ), or Fabaceae ( Inga ) recurred several times, but we did not recognize any clear patterns in relation to habitat preferences of the more prevalent tree species in the topographic gradients under study (Morera‐Beita et al., ). This tentative survey indicates rather unspecific host–plant associations to predominate among indicator moth species found in the three forest habitat types.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…However, the clear majority of our indicator species turned out to be host plant generalists, whereas only 23 species (25%) have taxonomically restricted host plant ranges. Among the few indicator species with narrow larval host ranges (one plant family or even one plant genus), affiliations to Moraceae, Urticaceae ( Cecropia ), or Fabaceae ( Inga ) recurred several times, but we did not recognize any clear patterns in relation to habitat preferences of the more prevalent tree species in the topographic gradients under study (Morera‐Beita et al., ). This tentative survey indicates rather unspecific host–plant associations to predominate among indicator moth species found in the three forest habitat types.…”
Section: Discussionmentioning
confidence: 65%
“…A foregoing study conducted in the same region reported similarly strong differences in plant community composition among forest plots in relation to topography, successional stage, and disturbance regime (Morera‐Beita et al., ). Based on a subset of the most abundant plant species, especially creek forests exhibited a plant species composition very distinct from forest plots located on ridges and slopes.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations